(untitled) (Ibrahim Cardiac Medical Journal, 2017)
Background & Objective: Patent ductus arteriosus (PDA) is a common condition in preterm infants and is associated with profound morbidity and mortality. Pharmacotherapy (indomethacin or ibuprofen) is the first choice to close the PDA, but if pharmacological closure is contraindicated or failed, surgical ligation is usually performed. But following surgical ligation of PDA, preterm infants may develop severe hypotension and respiratory failure. Prophylactic stress hydrocortisone (HC) has emerged as a therapy to prevent complications, although its efficacy in reducing postoperative hypotension and oxygenation difficulties has not been rigorously tested. The purpose of this study was to compare the outcomes in preterm infants who received stress HC before their PDA ligation to those who did not (standard treatment group or control). Materials & Methods: This comparative clinical trial was conducted in Dhaka Shishu Hospital (DSH), Dhaka over a period of 15 months between April 2014 to June 2015. A total of 40 infants with a significant PDA and a history of failed medical treatment were included in the study and were divided into two groups (each group having 20 infants) – one receiving stress HC before PDA ligation (Case) and the other did not (Control). Respiratory support, expressed as highest FiO2, highest mean airway pressure and mode of ventilation, was noted as was cardiovascular support including inotropic medication, its dose throughout the preoperative and the postoperative periods. Post-operative cardiovascular and respiratory supports were the main outcome measures which were measured within 72 hours following PDA ligation. Result: At baseline both the study groups were almost similar with respect to their sex, gestational age, birth weight, and age at surgery and prenatal steroid exposure. However, there was more incidence of preoperative steroid exposure in standard treatment group. Urine output was somewhat higher in the standard treatment group compared to the HC group but it was not statistically significant (1.33 vs. 1.21 ml/kg/min, p = 0.205). The mean arterial pressure was higher in the HC group than that in the standard treatment group (92.5 vs. 86.7 mmHg, p = 0.018), but it was clinically insignificant. The study observed that infants who received stress dose HC rarely needed vasopressor support post ligation and their average and highest doses of dopamine were also significantly lower compared to their standard treatment group. The postoperative high-frequency ventilation was more often needed in the standard treatment group, although none in either group needed this support preoperatively. The mean airway pressure was although similar in both groups the highest FiO2 was much less in the HC group. Conclusion: The study concluded that stress dose HC given to preterm infants before surgical ligation of PDA may improve the postoperative cardiorespiratory outcomes. But as the sample size was too small, this finding requires validation by large-scale study. Ibrahim Card Med J 2015; 5 (1&2): 9-14